О влиянии семантики основы на ее словообразовательную валентность - Англицкас, В. (Kalbotyra, 1978)
The analysis of nouns motivated by personal nouns shows that there is a set of selection rules in modem English word-building which are based on the semantics of stems. They manifest themselves in different combining abilities of stems belonging to different lexical groups with synonymous suffixes.